Structural And Thermal Characteristics of Aluminum Grades 6063 and 7075 with Application of Nano Coatings - Sridhar Yesaswi, Ch; Venkata Sai, N; Vivek, K; Raju, B; Venkat, G (International Journal of Engineering and Technology, 2018)
To fabricate any product, material selection is one of the major constraints for many engineers even on today. An intensive research is being done by scientists and engineers over the properties and characteristics of the materials. Due to the technology advancement, applications of various new products are entering into market with different materials. From the past few decades composites and alloy materials are playing a vital role because of their unique nature. In the present work heat exchangers are taken into application. In nuclear and power plants heat exchangers plays a crucial role in cooling the reactors. When these are made to cool with water by sending through metal pipes over a period of time, metal pipes get easily corroded because of water and thermal conductivity of the metal. When base metals are coated with Nano-particles there is a drastic change in their behavior. In this paper Aluminum grade 6063 and grade 7075 are considered and coated with Al2O3-NaOH Nano fluids. Their thermal and structural characteristics are identified before and after Nano coating.Â Â Â